Double Spiral Dupuytren's Disease: Case of Ulnar and Radial Spiral Cords in Shared Digit. Issue 10 (October 2020) - Kator, Jamie; Gopinath, Rohan; Miller, Nathan; Pensy, Raymond
Abstract : Summary: Dupuytren's disease is a benign fibroproliferative disorder resulting in progressive contraction of palmar and digital fascia. Diseased fascia of the hand condenses into tensile cords, manifesting in various anatomical combinations. The spiral cord variant is especially troublesome, as the cord travels under the digital neurovascular bundle and places it at risk during surgical resection. In severe cases, limited fasciectomy is required to release contracture and restore finger extension. Here, we present the case of a 79-year-old right-handed man with a history of severe Dupuytren's disease of both hands, who was found to have ulnar and radial spiral cords in his right ring finger. Diseased tissue was removed en bloc, restoring extension and function. To our knowledge, this is the first case of a digit with two spiral cords affecting both neurovascular bundles. It is important to be aware of the anatomical variations possible in Dupuytren's disease to avoid iatrogenic injury.